2009
DOI: 10.1128/mcb.01448-08
|View full text |Cite
|
Sign up to set email alerts
|

Two Classes of Dosage Compensation Complex Binding Elements along Caenorhabditis elegans X Chromosomes

Abstract: Dosage compensation equalizes X-linked gene products between the sexes. In Caenorhabditis elegans, the dosage compensation complex (DCC) binds both X chromosomes in XX animals and halves the transcription from each. The DCC is recruited to the X chromosomes by a number of loci, rex sites, and is thought to spread from these sites by an unknown mechanism to cover the rest of the chromosome. Here we describe a novel class of DCC-binding elements that we propose serve as "way stations" for DCC binding and spreadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Earlier low-resolution studies with X-chromosome DNA attached to an autosome showed that DCC did not spread such that the autosome was engulfed [14, 16, 19, 20]. We investigated different hypotheses for how DCC spreading onto the whole autosome is limited (Figure 5A).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Earlier low-resolution studies with X-chromosome DNA attached to an autosome showed that DCC did not spread such that the autosome was engulfed [14, 16, 19, 20]. We investigated different hypotheses for how DCC spreading onto the whole autosome is limited (Figure 5A).…”
Section: Resultsmentioning
confidence: 97%
“…For example, there is a ChIP-defined DCC focus 173 kb from the end. Regardless, the gradual decline of binding from the fusion site explains the need to have multiple recruitment elements or “way stations” [19] spaced along the X chromosome to maintain the required levels of DCC association with X.…”
Section: Resultsmentioning
confidence: 99%
“…The DCC is composed of a condensin I-like complex (known as condensin I DC ) and another five-subunit complex containing SDC-1, SDC-2, SDC-3, DPY-21, and DPY-30. Experiments combining genome-wide chromatin precipitation assays have revealed that the DCC is enriched at ;1500 sites scattered along the length of the X chromosomes that can be categorized into two different classes: rex (recruiting element on X) sites and dox (dependent on X) sites (McDonel et al 2006;Ercan et al 2007;Blauwkamp and Csankovszki 2009;Jans et al 2009). The rex sites contain a 12-base-pair sequence motif called MEX (motif enriched on X) and are able to recruit the DCC when detached from the X.…”
Section: Dosage Compensation In C Elegansmentioning
confidence: 99%
“…The DCC is thought to load across X chromosomes in a two-step manner: binding to a group of high-affinity recruitment sites (rex) and spreading in a transcription-dependent, DNA sequence-independent manner to sites unable to recruit on their own (dox) (15,32). Some rex sites are able to recruit only as extrachromosomal arrays and not as part of a duplication of a small region of X chromosomes (waystations) (5). Condensin I DC is homologous to condensin, the highly conserved mitotic chromosome organization and segregation machinery, suggesting that dosage compensation in the worm is achieved by partial condensation of the X chromosomes.…”
mentioning
confidence: 99%